Crystallization behaviour and lamellar thickness distribution of metallocene‐catalyzed polymer: Effect of 1‐alkene comonomer and branch length. (17th November 2016) - Daud, Muhammad; Shehzad, Farrukh; Al‐Harthi, Mamdouh A.
Abstract: The effect of comonomer and branching on the melt crystallization and lamellar thickness distribution was studied for ethylene and 1‐alkene copolymers. The comonomers used in this study are 1‐hexene, 1‐octene, and 1‐decene. A notable influence of the comonomer ratio in the feed was observed on the crystallization and melting behaviour. The Ozawa and Mo models were found suitable for these copolymers. However, variation of relative crystallinity at different heating rates preferred the Mo method over the Ozawa method. The melting behaviour and lamellar thickness distribution of the copolymers were analyzed by the help of the modified Gibbs‐ Thomson equation. The activation energies ( EA ) for the melt crystallization were calculated using the Kissinger method. It was observed that 1‐hexene comonomer exhibits lower EA, indicating an easier crystallization process as compared to other comonomers used. Overall, crystallization was found to be more influenced by the degree of branching rather than the comonomer type. Abstract : Effect of cooling rates and 1‐decene comonomer compositions on the melt crystallization of LLDPE.